Flipbook on Indonesian cultural diversity to enhance learning outcomes for fourth graders - Hilda Kusumaningtyas; Ali Sunarso (Research and Development in Education (RaDEn), 2024)
Researchers have conducted observations at SDN Denanyar 3 Sragen and obtained problematic results, namely limited learning media and low student learning outcomes in Social Sciences subjects. This study aims to develop, test the feasibility, and effectiveness of the learning media Flipbook Indonesian Cultural Diversity. The type of method used in this research is Research and Development (R&D) with the Bord and Gall development model which has 10 steps and researchers only use 9 steps. The validity test of the product being developed was carried out by material and media expert lecturers as examiners of the learning media "Indonesian cultural diversity flipbook". Results of this research include: 1.) the process of developing Flipbook media as a learning medium on Indonesian cultural diversity material, 2.) the feasibility of the Indonesian cultural diversity Flipbook media was assessed as very valid by two material and media experts validators with an average validation score of 90 .5%, 3.) t-test results show a sig value (2-tailed) 0.000 < 0.005, so there is a difference in the average results before the pretest and in the limited test and broad test, thus it can be concluded that the media can improve the learning outcomes of class IV students at SDN Denanyar 3.